A wobbly road to drug resistance in melanoma: tRNA‐modifying enzymes in translation reprogramming - McMahon, Mary (EMBO J, 2018)
Alterations in transcript‐specific translation are emerging as a driver of cellular transformation and cancer etiology. A new study provides evidence for enhanced codon‐dependent translation of hypoxia‐inducible factor 1α in promoting glycolytic metabolism and drug resistance in melanoma cells. This specialized translation reprogramming relies, in part, on mTORC2‐mediated phosphorylation of enzymes modifying the wobble position of the transfer RNA anticodon.